The Impact of Non-Governmental Organization and Social Entrepreneurship on Education Dropout: Empirical Study on Eltatwaa Hayat Association in Alexandria - Salama, Heba Ahmed; Ragheb, Mohamed A.; Wahba, Mohamed; Hemeida, Fahd Abdelaziz (The Arab Journal of Administration, 2024)
The purpose of this research is to empirically investigate the relation among school related factors, socio-economic constraints and education drop out considering student academic performance as a mediator and existence of NGO with social entrepreneurship unit as a moderator. A case study on Eltatwaa Hayat Association in Alexandria, Egypt. The study followed the quantitative approach and data gathered from a survey and the participants of the study were 421 parents in the selected NGO, data were obtained through questionnaires. The results were analysed employing by structural equation model analyses (SEM) using AMOS software. The main conclusions drawn from this study are: The direct effect among School related factors and Education dropout is statistically significant, the direct effect Socio-Economic and Education dropout is statistically significant, the direct effect School related factors and Student Academic Performance is statistically significant, the direct effect among Socio-Economic and Student Academic Performance is statistically significant, the direct effect among Student Academic Performance and Education dropout is statistically significant. In addition to that, the partial mediation of student academic performance among the independent variables and education dropout is statistically supported. Finally, the existence of Ngo with social entrepreneurship unit is statistically found as a moderator.